Designed Surface Topographies Control ICAM-1 Expression in Tonsil-Derived Human Stromal Cells - Vasilevich, Aliaksei S.; Mourcin, Frédéric; Mentink, Anouk; Hulshof, Frits; Beijer, Nick; Zhao, Yiping; Levers, Marloes; Papenburg, Bernke; Singh, Shantanu; Carpenter, Anne E.; Stamatialis, Dimitrios; Blitterswijk, Clemens van; et al. (Frontiers in Bioengineering and Biotechnology, 2018)
Fibroblastic reticular cells (FRCs), the T-cell zone stromal cell subtype in the lymph nodes, create a scaffold for adhesion and migration of immune cells, thus allowing them to communicate. Although known to be important for the initiation of immune responses, studies about FRCs and their interactions have been impeded because FRCs are limited in availability and lose their function upon culture expansion. To circumvent these limitations, stromal cell precursors can be mechanotranduced to form mature FRCs. Here, we used a library of designed surface topographies to trigger FRC differentiation from tonsil-derived stromal cells (TSCs). Undifferentiated TSCs were seeded on a TopoChip containing 2176 different topographies in culture medium without differentiation factrs, then monitored cell morphology and the levels of ICAM-1, a marker of FRC differentiation. We identified 112 and 72 surfaces that upregulated and downregulated, respectively, ICAM-1 expression. We discovered correlations between ICAM-1 expression, cell shape and design of surface topographies and confirmed our findings by using flow cytometry. Our findings confirmed that TSCs are mechano-responsive cells and identified particular topographies that can be used to improve FRC differentiation protocols.